Eksplorasi Sumber Daya Genetik Jagung Lokal Bali - PRADNYAWATHI, NI LUH MADE; WIJAYA, I KETUT ARSA; SUTEDJA, I NYOMAN (Agrotrop : Journal on Agriculture Science, 2022)
Genetic diversity of genetic resources is the basic material for producing superior varieties. These genetic resources can be in the form of local varieties, among others. The purpose of this study was to explore the types of local corn in the province of Bali. The method used was a survey method. The primary data collection techniques were observation and interviews and the secondary data in the form of literature study. The types of local corn obtained were then collected. Exploration was carried out at corn planting centres from August 2020 to November 2020. From the exploration results were found 16 local corn types. In Buleleng Regency, four local corn accessions were found, namely: Pangkung Paruk Barak corn, Pangkung Paruk Putih corn, Local Sambirenteng corn and Cicih Kebo corn. In Karangasem Regency, three local corn were found, namely Seraya corn, Purwakerti Putih corn and Ketan Bunutan corn.  In Klungkung Regency, one type of local corn was found, Local Nusa Penida corn. In Bangli Regency, six types of local corn were found, namely Kuning Pengootan corn, Local Landih corn, Panes corn/Kuning Daup corn, Injin Daup corn, Bali Malet Gusti corn and Barak Keliki Kintamani corn. In Badung Regency, two types of local corn were found, namely Belok Sidan corn, and Ketan Belok Sidan corn.